PERBANDINGAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL DISCOVERY LEARNING DENGAN PROBLEM BASED LEARNING - Uswatun Hasanah; Chandra Ertikanto; Ismu Wahyudi (Jurnal Pembelajaran Fisika, 2017)
This research aimed to compare the learning outcomes in some aspects, such as cognitive aspect, scientific attitude, and science process skills of students. The topic was Circular Motion. This research organized at Senior High School 2 Pringsewu, on 1th semester in 2016/2017 using Pretest and Posttest Equivalent Group Design as the research design. Discovery learning model as first experimental class and problem based learning as second experimental class. Base on research, the average value of the cognitive study with N-gain from both classes were 0.44 and 0.42, then the average value of science process skills was 53.44 and 55.63, and the average value of scientific attitude was 79.49 and 83.58. These results indicated that there was no any difference between cognitive study and science process skills students in both of the experimental class, and scientific attitude aspect of problem based learning class was higher than discovery learning class.Penelitian ini bertujuan untuk mengetahui perbandingan hasil belajar pada ranah kognitif, sikap ilmiah, dan keterampilan proses sains siswa pada materi gerak melingkar. Penelitian ini dilakukan di SMA Negeri 2 Pringsewu, pada semester ganjil tahun ajaran 2016/2017, dengan desain penelitian Pretest Posttest Equivalent Group Design. Model discovery learning sebagai kelas eksperimen 1 dan Problem Based Learning sebagai kelas eksperimen 2. Berdasarkan penelitian yang telah dilakukan, diperoleh hasil rata-rata nilai kognitif dengan N-gain kedua kelas eksperimen adalah 0,44 dan 0,42, hasil rata-rata nilai KPS adalah 53,44 dan 55,63, dan hasil rata-rata nilai sikap ilmiah adalah 79,49 dan 83,58. Hal ini menunjukkan tidak terdapat perbedaan hasil belajar kognitif dan KPS pada kedua kelas, sedangkan sikap ilmiah kelas problem based learning lebih tinggi dari discovery learning.Kata kunci: discovery learning, problem based learning, hasil belajar